Peripheral Inflammation Results in Increased Excitability of Capsaicin-Insensitive Nociceptive DRG Neurons Mediated by Upregulation of ASICs and Voltage-Gated Ion Channels - Duzhyy, Dmytro E.; Voitenko, Nana V.; Belan, Pavel V. (Frontiers in Cellular Neuroscience, 2021)
Previously, we have characterized the capsaicin-insensitive low pH-sensitive (caps−lpH+) subtype of small-sized nociceptive dorsal root ganglion (DRG) neurons that express acid-sensing ion channels, T-type Ca2+ channels, and have isolectin B4-negative phenotype. These neurons demonstrated increased excitability in a model of long-term diabetes, contributing to chronic pain sensation. Here we studied changes in the excitability of the caps−lpH+ neurons and underlying changes in the functional expression and gating properties of ion channels under complete Freund's adjuvant (CFA)-induced peripheral inflammation. We have found that, under these pathological conditions, the functional expression of the acid-sensing ion channels (ASICs) and voltage-gated Na+ channels, was increased. In addition, T-type Ca2+ current was significantly increased in the neurons at the membrane potentials close to its resting value. Altogether, the observed changes in the channel functioning shifted a pH level evoking an action potential (AP) toward its physiological value and led to an increase of evoked and spontaneous excitability of the caps−lpH+ neurons that may contribute to hyperalgesia and chronic inflammatory pain.